ANALISIS DATA PENJUALAN PADA SUPERMARKET XYZ MENGGUNAKAN METODE MARKET BASKET - Ananda Azizul Akbar; Akbar Bintang Izzulhaq; Nafilah Nursabila; Valentinus Roby Hananto (Program Studi Sistem Informasi, Universitas Banten Jaya, 2023)
The economic growth in Indonesia has increased significantly, positioning Indonesia as the 4th largest economy after China, India, and Malaysia. This is also accompanied by national retail sales reaching a total of Rp6,044 trillion. One example of a retail business in Indonesia is Supermarket XYZ, which operates in Indonesia and sells essential items such as sugar, eggs, butter, and others. This research discusses an issue that exists in Indonesia, for example, Supermarket XYZ. The supermarket faces a problem with its employees struggling to determine the appropriate product layout based on consumer purchasing behavior. The market basket analysis method is used in this research to assist Supermarket XYZ's employees in determining the product layout. Transaction data is collected through internet searches, specifically on the Kaggle website. The data is then processed using the market basket analysis method, both manually and with the aid of the RapidMiner tool, to ensure the validity of the calculations. Once obtained, the results are implemented into a program to provide predictions for product placement layout. The research findings show that out of the 10 most purchased products by consumers, the top four products are chocolate, apples, bread, and ice cream. Furthermore, the suitable product combinations for layout placement yield 3 combinations: chocolate placed near apples with a support rate of 23%, chocolate placed near bread with a support rate of 22%, and chocolate placed near ice cream with a support rate of 21%.